Effectiveness Of Using Elastic Wrist Splints on The Productivity of Cigarette Rollers with Wrist Pain at Gama Cigarette Company, Karanganyar - Muhammad Syaifuddin; Muhibbah Fatati; Enif Marsa Waluyo (Health Research Journal of Indonesia, 2026)
Human resources are a crucial factor in increasing work productivity, especially in companies that still employ manual labor, such as cigarette rolling. Prolonged repetitive wrist activities can lead to musculoskeletal pain, which can reduce productivity. The use of elastic wrist splints aims to reduce pain and improve performance. This study aimed to determine the effectiveness of elastic wrist splints on the productivity of cigarette rollers experiencing wrist pain at the Gama Cigarette Company in Karanganyar. This study used a quasi-experimental method with a one-group pre-test and post-test design. A sample of 25 respondents was selected using purposive sampling. Productivity was measured based on daily production volume, with a minimum standard of 4,500 cigarettes per day. The intervention, which involved the use of elastic wrist splints, was administered for two weeks. The results showed an increase in productivity after using elastic wrist splints, with an average score increasing from 2.12 to 3.12. A Wilcoxon test showed a p-value of 0.000 (p ≤ 0.05), indicating a significant difference between before and after the intervention. The conclusion of this study is that the use of elastic wrist splints is an effective non-pharmacological intervention for increasing the productivity of cigarette rollers experiencing wrist pain. The reduction in pain contributes to improved work performance, enabling the achievement of production targets and even exceeding the company's minimum production standards.